Status of greenhouses in Khartoum and Gezira States, Sudan - Ibrahim, Sahar S.; Elamin, Osman M.; Elkashif, Mohammed E.; Abdalla, Abdalla S. (Gezira Journal of Agricultural Science, 2016)
Greenhouse technology facilitates the cultivation of most horticultural crops in any region of the world, provided that the greenhouse is properly designed and equipped to control environmental conditions. The objective of this study was to investigate the characteristics of greenhouses in Khartoum and Gezira States, Sudan, and show their drawbacks and disadvantages.  A survey was carried out using a questionnaire and interviews with greenhouse owners in Khartoum and Gezira States. Khartoum and Gezira States have about 68 greenhouse projects, 33 of them were selected for the study. The data were collected during 2013 and were analyzed using statistical package for social sciences (SPSS) computer program. Results showed that 69.7% of greenhouses were privately owned and the vast majority of greenhouses were used to produce vegetable crops or seedlings. Results indicated that most of the greenhouses designs are not suited to the hot arid tropics of the Sudan. More than half of greenhouses had the arched system, most of them were covered by polyethylene, 69.7% of greenhouses were constructed in a single span, 72.7% had a single door, 76.3% of greenhouses had a height between 2.5 m to 3 m and 42.6% of them were 40 m long. Accordingly, an ideal greenhouse design is needed in which all the drawbacks and shortcomings are corrected to suit the arid conditions of central Sudan.